Study of amino-acid structure Lemna minor L - L. A. Nikiforov; M. V. Belousov; N. S. Fursa (Бюллетень сибирской медицины, 2011)
For the first time qualitative and quantitative amino-acid structure Lemna minor L. is studied with use of a highly effective liquid chromatography. Presence 18 proteinogennic amino acids, including 8 irreplaceable is established. The sum of replaceable amino acids of a duckweed small is presented monoaminocarboxylic,monoaminodicarboxylic, diaminomonocarboxylic and heterocyclic acids. Irreplaceable amino acids are presented monoaminomonocarboxylic and diaminomonocarboxylic by acids.